2016
DOI: 10.1111/luts.12161
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Exposure During Videourodynamics: Establishing Risk Factors

Abstract: We have shown that increased radiation exposure as measure with Dose Area Product during VUDS was significantly associated with larger BMI, female gender, larger bladder capacity, presence of VUR, junior operator, and higher number of fill cycles. Further studies are now underway to attempt to reduce exposure based on these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This is likely secondary to difficulties with positioning and adequate penetration of the X-ray to capture images of appropriate quality. This is consistent with prior findings at the same institution before protocol initiation, 8 as well as with other studies in women and children undergoing VUD. 15,16 Similarly, studies looking at radiation during spinal surgery have found that patients with a BMI greater than 25 have a 30% increase in fluoroscopy time which may be explained by the lower quality of images and difficulty in image acquisition due to tissue penetration and scatter.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is likely secondary to difficulties with positioning and adequate penetration of the X-ray to capture images of appropriate quality. This is consistent with prior findings at the same institution before protocol initiation, 8 as well as with other studies in women and children undergoing VUD. 15,16 Similarly, studies looking at radiation during spinal surgery have found that patients with a BMI greater than 25 have a 30% increase in fluoroscopy time which may be explained by the lower quality of images and difficulty in image acquisition due to tissue penetration and scatter.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, before the implementation of a standardized protocol, female sex was found to be an independent risk factor for increased radiation exposure which was previously attributed to the decreased clarity of fluoroscopic images in the seated position which may require repeat spot images or longer fluoroscopic time. 8 Additionally, while there was no prior protocol dictating that images be taken during Valsalva to assess for fluoroscopic evidence of SUI this was done by many operators and may have contributed to radiation exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations